Kaligrafi Islam: Dari Nalar Seni hingga Simbolisme Spiritual - Islah Gusmian (Al-Jami'ah: Journal of Islamic Studies, 2003)
This article reveals the history of the rise and the development of calligraphy in Islam. By referring to the history and texts of al-Quran, this articles shows that Islamic calligraphy have undergone some significant development because of the textual effect of al-Quran and the al-Sunnah which highlight the necessity of calligraphy for Muslims. The prohibition of drawing living things raised by fuqaha in the medieval age even intensified the development of calligraphy. Then, in its development, Islamic calligraphy is not only an artistic expression of Muslims, but, for centuries, the Sufi have been taken the wisdom (hikmah) of spiritual aspects of calligraphy. Some of them talked about the symbol of scrip/letters and words, about the detail shapes of scripts, and some other explained in detail the teaching principle of the existence through the symbols of ink and pen. This article emphasis that the beauty of Islamic calligraphy does not only touch the artistic dimension with all its various type, but also it intertwines intensively with the doctrine of esoteric, aspect of Islam